Perlindungan Hak Anak: Upaya Pencegahan Kekerasan Anak Melalui Kebijakan Sekolah Ramah Anak - Dewi, Anak Agung Istri Ari Atu (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the setting of childfriendly schools to prevent child violence and the standardsetting model for child-friendly schools to protect children’s rights. This study used normative legal research with statutory regulations, concept approaches, and analytical approaches. Collection of secondary legal materials used document study techniques. The data that had been obtained was analyzed using an interpretation technique, namely legal hermeneutics. The study results showed that child-friendly schools were indicators of child-friendly district or city development by the Regulation of the Minister of Women’s Empowerment and Child Protection Number 11 of 2011 to protect children’s rights from violence in the educational environment. The standardization of child-friendly school development based on the Minister of Women’s Empowerment and Child Protection Regulation Number 8 of 2014 required essential components, including policies, curriculum implementation, educators and education personnel trained in children’s rights, child-friendly learning processes, child-friendly facilities and infrastructure, child participation, as well as the involvement of parents, alumni, community organizations, and the business world.